(untitled) (Iranian Journal of Kidney Diseases, 2018)
Introduction. Data on the effects of coenzyme Q10 (CQ10) on gene expression related to insulin, lipid, and inflammation in patients with diabetic nephropathy (DN) are scarce. This study aimed to determine the effects of CQ10 supplementation on gene expression related to insulin, lipid, and inflammation pathways in patients with DN. Materials and Methods. Forty patients with DN, aged 40 to 85 years old, were randomly assigned into 2 groups to receive either 100 mg/d of CQ10 supplements (n = 20) or placebo (n = 20), for 12 weeks. Gene expression related to signaling pathway of insulin, lipid, and inflammation were determined in blood samples using a reverse transcriptase polymerase chain reaction method. Results. Quantitative results of reverse transcriptase polymerase chain reaction demonstrated that compared with the placebo, CQ10 administration upregulated gene expression of peroxisome proliferator-activated receptor-γ (P = .02) in peripheral blood mononuclear cells of the patients with DN. In addition, compared with the placebo, CQ10 supplementation downregulated gene expression of interleukin-1 (P = .003) and tumor necrosis factor-α (P = .02). No significant effects were observed on gene expression of oxidized low-density lipoprotein, lipoprotein(a), glucose transporter-1, transforming growth factor-β in the CQ10 group. Conclusions. Overall, CQ10 supplementation for 12 weeks in DN patients significantly improved gene expression of peroxisome proliferator-activated receptor-γ, interleukin-1, and tumor necrosis factor-α.